2008
DOI: 10.1080/15250000802329370
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Affect Specificity in Infants' Use of Emotion Cues

Abstract: This study examined the emergence of affect specificity in infancy. In this study, infants received verbal and facial signals of 2 different, negatively valenced emotions (fear and sadness) as well as neutral affect via a television monitor to determine if they could make qualitative distinctions among emotions of the same valence. Twenty 12‐ to 14‐month‐olds and 20 16‐ to 18‐month‐olds were examined. Results suggested that younger infants showed no evidence of referential specificity, as they responded simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Whereas at 12 months of age, children’s toy play was inhibited by a peer’s affective responses to the toys, 18-month-old children were not responding systematically to a peer’s emotions. Other research using similar procedures has demonstrated that children at this age do display appropriate responses to a televised adult’s fear (Martin et al, 2008), so it appears that peer emotion informants are not helpful in 18-month-olds’ decisions about playing with novel toys. We were unable to probe in the current study whether this is because 18-month-olds failed to understand the peer’s affective message, or whether they did not know how to respond to the peer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas at 12 months of age, children’s toy play was inhibited by a peer’s affective responses to the toys, 18-month-old children were not responding systematically to a peer’s emotions. Other research using similar procedures has demonstrated that children at this age do display appropriate responses to a televised adult’s fear (Martin et al, 2008), so it appears that peer emotion informants are not helpful in 18-month-olds’ decisions about playing with novel toys. We were unable to probe in the current study whether this is because 18-month-olds failed to understand the peer’s affective message, or whether they did not know how to respond to the peer.…”
Section: Discussionmentioning
confidence: 97%
“…This result stands in contrast to studies that have employed similar methods but used a televised adult as the emotion informant instead of an older peer. For example, Mumme and Fernald (2003) found that 12-month-olds systematically decreased their touch to the target toy after they had watched an adult display fear toward it, although other labs have not always replicated this effect (Martin, Witherington, & Edwards, 2008). The current results suggest that 12-month-olds may, at the very least, discriminate between emotion informants of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…During the early years; children use emotional clues of parents as social references (Moses et al, 2001;Mumme et al, 2007;Mumme et al, 1996;Repacholi & Gopnik, 1997;Stenberg, 2003;Stenberg & Campos, 1990;Stenberg et al, 1983;Striano & Rochat, 2000;Vaish & Striano, 2004). As they experience, children notice that their emotional reactions may change and learn how to comment on emotions in time, to express them as desired and to control these emotions (Martin et al, 2008;Saarni, 1999Saarni, & 2000Saarni et al, 2007).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Typically, by 12 months of age infants are able to link specific objects or events with another person's emotional messages (Hertenstein & Campos, 2004;Moses, Baldwin, Rosicky, & Tidball, 2001;Mumme & Fernald, 2003) and actively seek out emotional information from others to guide their actions toward those objects and events in meaningful ways (Campos & Sternberg, 1981;Feinamn, 1982). Furthermore, by 16 months of age infants respond differently to objects referenced with emotional expressions of a similar (fearful vs. sad) valence, indicating further refinement of social cognitive competencies (Martin, Witherington, & Edwards, 2008). However, few studies have examined how context or type of stimulation influences infants' ability to successfully perform a social referencing task, particularly in early infancy.…”
Section: Social Referencingmentioning
confidence: 99%
“…First, most social referencing studies have tested infants of 12 to 18 months of age (Hornick & Gunnar, 1988;Kim, Walden, & Knieps, 2010;Martin, Witherington, & Edwards, 2008;Moses, Baldwin, Rosicky, & Tidball, 2001;Mumme, Fernald, & Herrera, 1996;Vaish & Striano;Zarbatany & Lamb, 1985), however, this study focused on the emergence of social referencing and tested infants in the first half year of life.…”
Section: Significancementioning
confidence: 99%